The interactive effects of deer herbivory and flooding on tree recruitment in floodplain forests of the Upper Mississippi River system - Cogger, Benjamin J. (My University, 2011)
Floodplain forests are a critical link between land and river ecosystems, moderating nutrient fluxes, providing animal habitat, and stabilizing the river corridor. In the Upper Mississippi River (UMR), floodplain tree recruitment appears to be limited by whitetailed deer browsing. The effects of landscape position and species composition on deer activity in floodplain forest restoration sites were examined, along with the ways in which deer browsing and flooding interact to affect the growth of young trees.
Keywords: Mississippi River.; Whitetail deer.; Habitat selection.; Wetland conservation.; Population biologry.; Herbivores; Ecology.